Readiness For The Implementation Of Electronic Medical Records - Suchi Rahmadani; Ahmad Amiruddin; Mansyur (International Journal of Multidisciplinary Learners, 2025)
Electronic Medical Records are used in health care facilities to fulfill various purposes. Electronic Medical Record users are an important aspect of realizing the ideal Electronic Medical Record. This study aims to determine the readiness of Electronic Medical Record implementation in South Buton Regency Hospital in 2024. This research was conducted at the South Buton Regency Hospital in 2024. The method used is using a descriptive type of approach with a qualitative approach and the method of data collection techniques using interview methods, and observation. Data collection tools using interview guidelines, observation sheets. In the aspect of human resources, medical recorders at the South Buton District Hospital are quite ready, this is based on the availability of IT officers and the ability to run computers is quite good. In the aspect of Organizational Work Culture, South Buton Regency Hospital is quite ready, this is based on the involvement of other health workers besides medical record officers in the process of implementing electronic medical records and the availability of SIMRS. In the Governance Aspect, the leadership of South Buton District Hospital is quite ready, this is based on SIMRS planning, and currently SIMRS is available but still in the process of building menu features. However, procedures related to SIMRS usage policies are not currently available. In the Infrastructure Aspect at the South Buton Regency Hospital, it is quite ready, this is based on the availability of a budget in the process of implementing current medical records, although the number of supporting facility needs has not been met such as computers, printers, Wi-fi and other supporting tools.